Isolation of Endophytic Microbes from Gunung Halimun National Park, West Java, Indonesia and Bioassay Their Potency for Eradicating Microbial Crops Pathogen - Sukara, Endang; Melliawati, Ruth (Annales Bogorienses, 2013)
Gunung Halimun National Park